Analysis Of The Influence Of Leader Behavior And Public Health Center Management Processes On Immunization Program Performance At Kuala Bali Public Health Center, Serdang Bedagai - Syafrina Rachmi Yuana; Ermi Girsang; Liani Ginting (CV. Inara, 2023)
There are still deficiencies in the achievement of UCI (Universal Child Immunization) in villages/wards. This is due, among other things, to the lack of attention and support from various parties towards the immunization program. This study aims to analyze the influence of leader behavior and management of the health center on the performance of the immunization program at the Kuala Bali Health Center Serdang Bedagai. This type of research is a quantitative researchwith a cross sectional design. The location of this research was conductedinKuala Bali Health Center, Serdang Bedagai. The research population is all121 midwives in 17 sub-districts of the Kuala Bali Serdang Bedagai Health Center, and 1 person in charge of immunization services so that it consists of 122 people.The sample in the study amounted to 122 patients. Survey data were analyzed using the chi-square test and logistic regression. The results showed that there was an effect of decision making on performance, there was an effect of leadership style on performance, there was an effect of delegation of tasks on performance, there was an influence on how to communicate on performance, there was an influence on planning on performance, there was an effect on organizing on the performance of the immunization program, there was an influence on implementation on the performance of the immunization program, there is an influence of supervision on the performance of the immunization program at the Kuala Bali Serdang Bedagai Health Center. The variable that has the most influence on the performance of the immunization program at the Kuala Bali Serdang Bedagai Health Center is the organizing variable.The results of this study suggest thatThe results of this research are used as input for evaluating the implementation of the immunization program, in order to provide guidance to the leaders of the Public Health Center to improve their abilities in leader behavior and management processes, especially in organizing so that the performance of the midwives becomes even better.